Evaluasi Usability Pada Aplikasi BNI Mobile Banking Dengan Menggunakan Metode Usability Testing dan System Usability Scale (SUS) - Irfanda Mahardhika Hidayat Kusumawardhana; Niken Hendrakusma Wardani; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In an highly competitive of the banking world, Bank Negara Indonesia (BNI) trying to provide several services that can support customer needs, for example, BNI Mobile Banking. BNI Mobile Banking provides convenience services for making multiple transactions from a smartphone. However, there were usability problems discovered through observation and interviews including difficulties in finding proof of transaction, there is no period when entering numbers and some service menus are not in match with the type of service. Therefore, it is necessary to do research with three stages of research. the first stage does initial testing to measure the learnability metric, efficiency metric, error metric and satisfaction metric obtained using two methods there are Usability Testing and System Usability Scale (SUS). the second stage provides recommendations for improvement based on the results of the interview and follows the rules of google material design guidelines. the third stage does test the recommendations for improvements that have been made and compares the measurement results of usability metrics with the measurement results of usability metrics on the initial test. The recommendations for improvements can provide an increase in learnability metrics from 68% to 88%, an increase in efficiency metrics from 0.01 goals/sec to 0.05 goals/sec, a decrease in metric errors from 30% to 5% and an increase in satisfaction metrics from 62.67 to 74.25.